Clinicopathological Profile and Treatment Outcome of Renal Cell Carcinoma: A Review from a Tertiary Cancer Centre in North East India - S. Roy, Partha; Mittal, Hemant Kumar; Behera, Braja Gopal; Hazarika, Munlima; Dubey, Manas; Randhawa, Amritjot; Bhattacharya, Ankur; Medhi, Kakoli; Das, Gaurav; Bejbaruah, Rukmini (Asian Pacific Journal of Cancer Care, 2025)
Background and Objectives: Renal cell carcinoma (RCC) constitutes 4% of adult malignancies and 90% of kidney cancers. While extensively studied in Western populations, data from India particularly Northeast India remain limited. This retrospective study aimed to assess overall survival (OS), progression-free survival (PFS), and disease-free survival (DFS) among RCC patients treated at a tertiary cancer centre in Northeast India between January 2020 and December 2022. Materials and Methods: We retrospectively analyzed 88 RCC patients who received treatment. Clinical parameters, including age, sex, histology, stage, metastatic pattern, treatment, and outcomes, were recorded. Kaplan-Meier analysis was used for survival estimation. Prognostic factors were evaluated using univariate and multivariate analyses. Results: The majority had clear cell histology (85%), with a median age of 56 years and a male-to-female ratio of 3:1. Metastatic disease was present in 65%, commonly affecting the lungs (67%), bones (44%), liver (32%), and brain (10%). Among those with metastasis, 40% were classified as poor-risk according to IMDC criteria. All non-metastatic patients (n=31) underwent surgery (68% radical, 32% partial nephrectomy). Among metastatic patients (n=57), VEGFR tyrosine kinase inhibitors were commonly used sunitinib (n=22) and pazopanib (n=25); one received nivolumab-based immunotherapy. With a median follow-up of 17 months, metastatic RCC showed poor outcomes, with median PFS and OS of 9 and 12 months, respectively. Non-metastatic RCC had an 18-month OS of 80.5%, with median OS not reached. OS varied by IMDC risk: 30 months (favorable), 12 months (intermediate), and 6 months (poor) (p<0.001). Sunitinib and pazopanib had comparable efficacy overall, though sunitinib had superior OS in favorable-risk patients (51 vs. 28 months, p<0.0001). Conclusions: RCC patients in Northeast India often present younger and with advanced disease. VEGFR-TKIs remain standard in limited access to immunotherapy. Enhanced early detection and access to immunotherapy are vital to improve outcomes.